Extrasolar Planets And False Atmospheric Biosignatures: The Role Of Micrometeoroids - Court,RW; Sephton,MA (Planetary and Space Science, 2012)
The coexistence of oxygen and a reduced gas such as methane in the atmosphere of an extrasolar planet is considered to be strong evidence for the presence of a biosphere. Proposed spacecraft such as Darwin or Terrestrial Planet Finder are designed to be capable of spectroscopically characterising the atmospheres of exoplanets, detecting chemical disequilibrium indicative of life. However, methane can be produced by various abiological mechanisms, including the ablation of carbonaceous micrometeoroids upon atmospheric entry, and it is possible that extrasolar planets in dust-rich systems might receive enough micrometeoroidal infall to produce a false atmospheric biosignature. Here, we review the production of methane from carbonaceous meteoroids upon atmospheric ablation in our solar system and discuss its application to extrasolar planets. The current paucity of data regarding dust densities in systems possessing terrestrial planets in the habitable zones of their stars makes firm conclusions difficult. However, the data suggest that only very young systems possessing very dense debris disks, or systems undergoing reorganisation similar to the Late Heavy Bombardment in our early solar system, would be capable of producing sufficient methane to be mistaken for an atmospheric biosignature.